A math journey through planet Earth - Rooney, Anne (Rooney, Anne. Go figure!, 2015)
"Fun pictograms and infographics about planet Earth make learning about math topics such as volume, scale diagrams, division, and number lines easy and fun. In this book, readers go on a mission to protect threatened areas around the world and use their mathematical skills to measure geysers, protect forests, and check on glaciers. Math puzzles and exercises help children build confidence in their math skills"--Provided by publishers.